Influence of Project Scope Definition on Cost Overruns in Public Sector Projects in the Japan - Sakamoto, Yao (International Journal of Project Management, 2024)
Purpose: The aim of the study was to assess the influence of project scope definition on cost overruns in public sector projects in the Japan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that a well-defined project scope is crucial for establishing clear objectives, deliverables, and expectations, which can significantly mitigate the risk of cost overruns. Studies indicate that unclear or poorly communicated project requirements often lead to scope creep, where additional features or changes are introduced without corresponding budget adjustments, resulting in unexpected expenditures. Moreover, early stakeholder engagement and thorough risk assessment during the scope definition phase are essential for anticipating potential challenges that could escalate costs. Overall, effective scope management practices not only help control expenses but also enhance project performance and stakeholder satisfaction, highlighting the importance of diligent planning and communication in public sector projects. Implications to Theory, Practice and Policy: Systems theory, stakeholder theory and change management theory may be used to anchor future studies on assessing the influence of project scope definition on cost overruns in public sector projects in the Japan. The study encourage the implementation of standardized practices for scope definition and stakeholder engagement in public sector projects. The proposed recommendations advocate for the formulation of policies that standardize project management practices in the public sector.